History and evolution of regional anesthesiology and acute pain medicine fellowship training. Issue 4 (29th January 2020) - Shapiro, David Michael; Hargett, Mary J; Kopp, Sandra; Neal, Joseph M; Mariano, Edward R; Liguori, Gregory
Abstract : Introduction: In 2016, individual training programs in regional anesthesiology and acute pain medicine (RA/APM) became eligible for accreditation by the Accreditation Council for Graduate Medical Education (ACGME), thereby culminating a process that began 15 years earlier. Herein, we review the origins of regional anesthesia training in the USA, the events leading up to accreditation and the current state of the fellowship. Methods: We reviewed pertinent literature on the historical aspects of RA/APM in the USA, related subspecialty training and the formation and current state of RA/APM fellowship training programs. Additionally, a survey was distributed to the directors of the 74 RA/APM fellowships that existed as of 1 January 2017 to gather up-to-date, program-specific information. Results: The survey yielded a 76% response rate. Mayo Clinic Rochester and Virginia Mason Medical Center likely had the first structured RA/APM fellowships with formalized curriculums and stated objectives, both starting in 1982. Most programs (86%), including ACGME and non-ACGME fellowships, came into existence after the year 2000. Six responding programs have or previously had RA/APM comingled with another subspecialty. Eight current programs originally offered unofficial or part-time fellowships in RA/APM, with fellows also practicing as attending physicians. Discussion: The history of RA/APM training in the USA is a tortuous one. It began with short 'apprenticeships' under the tutelage of the early proponents of regional anesthesia and continues today with 84 official RA/APM programs and a robust fellowship directors' group. RA/APM programs teach skills essential to the practice and improvement of anesthesiology as a specialty.